Talking to the senses: modulation of tactile extinction through hypnotic suggestion - Maravita, Angelo; Cigada, Mario; Posteraro, Lucio (Frontiers in Human Neuroscience, 2012)
Following brain damage, typically of the right hemisphere, patients can show reduced awareness of sensory events occurring in the space contralateral to the brain damage. The present work shows that a hypnotic suggestion can temporarily reduce tactile extinction to double bilateral stimulation, i.e., a loss of contralesional stimuli when these are presented together with ipsilesional ones. Patient EB showed an improved detection of contralesional targets after a single 20-min hypnosis session, during which specific suggestions were delivered with the aim of increasing her insight into somatosensory perception on both sides of the body. Simple overt attention orienting toward the contralesional side, or a hypnotic induction procedure not accompanied by specifically aimed suggestions, were not effective in modulating extinction. The present result is the first systematic evidence that hypnosis can temporarily improve a neuropsychological condition, namely Extinction, and may open the way for the use of this technique as a fruitful rehabilitative tool for brain-damaged patients affected by neuropsychological deficits.